2009
DOI: 10.1149/1.3120709
|View full text |Cite
|
Sign up to set email alerts
|

Deconvolution of the Potential and Time Dependence of Electrochemical Porous Semiconductor Formation

Abstract: Access to the full text of the published version may require a subscription. Rights

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 23 publications
2
20
0
Order By: Relevance
“…This reflects the initial rapid increase in the density of pits which is arrested as domains merge into a continuous porous layer. [30][31][32][33][34][35][36][37][38][39][40] The separation of the pits along α is slightly larger than along β at all potentials. Presumably this asymmetry is due to the domain shape and the propagation of the initial primary pores (as shown in Fig.…”
Section: Side-to-basementioning
confidence: 84%
See 2 more Smart Citations
“…This reflects the initial rapid increase in the density of pits which is arrested as domains merge into a continuous porous layer. [30][31][32][33][34][35][36][37][38][39][40] The separation of the pits along α is slightly larger than along β at all potentials. Presumably this asymmetry is due to the domain shape and the propagation of the initial primary pores (as shown in Fig.…”
Section: Side-to-basementioning
confidence: 84%
“…When semiconducting materials are anodized, localized etching can occur leading to selective removal of material such that the remaining material forms a skeletal structure that encompasses a network of pores. In such a manner, Si, [8][9][10][11][12][13][14][15][16][17] SiC, [18][19][20] Ge, [21][22][23] Ge/Si alloys, 24 and various III-V compounds [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] (including InP) [27][28][29][30][31][32][33][34][35][36][37][38][39][40] can be made porous.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5][6] This is followed by some examples of research on lithium batteries and compound semiconductors at Bell Laboratories [7][8][9][10][11][12][13][14][15][16][17][18] beginning in 1979. I then discuss some of our work at the University of Limerick on electrochemical etching and nanopore formation on III-V semiconductors, [19][20][21][22][23][24][25][26][27][28][29][30] a particularly appropriate topic for this presentation in view of Professor Gerischer's 31 extensive pioneering contributions to semiconductor electrochemistry. Another topic on which I have worked is electrodeposition of copper metallization.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,38,43,44 We have previously shown that anodization of an n-InP electrode in >2 mol dm −3 KOH results in the formation of a nanoporous InP layer 3,[48][49][50][51] of finite thickness. [52][53][54][55][56] Further investigation showed that the porous region is capped by a thin layer (20-40 nm, depending on the conditions) close to the surface that appears to be unmodified. The fact that a porous region can form within the substrate by electrochemical oxidation despite this dense InP layer is explained by the presence of a relatively low areal density (typically ∼10 7 cm −2 ) of localized channels through the layer.…”
mentioning
confidence: 99%